PENGARUH CAPITAL INTENCITY RATIO DAN LEVERAGE TERHADAP MANAJEMEN LABA (PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Lesi Herlina Putri; Ela Widasari; Sri Intan Purnama (The Asia Pacific Journal Of Management Studies, 2024)
Financial statements are one source of information about the condition and performance of a company, many companies are carrying out certain strategies to be better and be able to compete. This study aims to analyze the effect of Capital Intensity Ratio (CIR) and Leverage (DAR) on Earnings Management. This study uses quantitative methods, with the type of data that is secondary data in the form of financial statements. The population used in this study are LQ45 companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020 as many as 45 companies. Samples were taken using the purposive sampling technique, where the LQ45 companies that were used as research samples were 13 companies with observations for 5 years, so the research sample obtained was 65 financial statement data. The data analysis technique in this study used the classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test and autocorrelation test, multiple linear regression analysis, hypothesis testing consisting of coefficient of determination, t test and F test using The results of this study partially show that there is a significant effect of the Capital Intensity Ratio (CIR) variable on earnings management while the Leverage (DAR) variable partially has no effect on earnings management. Simultaneously Capital Intensity Ratio (CIR) and Leverage (DAR) affect earnings management.